Control of Spatial Utilization in the Spatial Plan Policy: Case of Ambarawa Ring Road Semarang Regency (Faculty of Law Universitas Negeri Semarang, 2022)
The Regional Regulation of Semarang Regency Number 6 of 2011 Article 61 states that the provisions on the conversion of land functions, especially on irrigated rice fields to non-agricultural land, except for general development purposes, are allowed but must refer to the law. Population development causes people to often use space that is not in accordance with regulations, namely by utilizing space in food crop farming areas for the construction of commercial business buildings as happened in the Ambarawa Ring Road area. The purpose of this study is to determine the factors that cause the establishment of buildings that are not in accordance with spatial planning and to determine law enforcement on controlling space utilization. This study uses a qualitative research method with a sociological juridical approach. While the types and sources of data are primary data and secondary data. The results of the study stated that in the use of space in the food crop agricultural area in the Ambarawa Ring Road area, it was found that in the area there were violations of land conversion to non-agricultural activities with the presence of several buildings for commercial business activities. The conclusion is that law enforcement on controlling the use of space in the Ambarawa Ring Road area is not optimal. The directions for imposing sanctions in the Semarang Regency Regional Regulation Number 6 of 2011 are not implemented properly.